Workers' Remittances and the Equilibrium Real Exchange Rate : Theory and Evidence - Chami, Ralph; Barajas, Adolfo; Hakura, Dalia; Montiel, Peter (Washington, D.C. : International Monetary Fund, 2010)
This paper investigates the impact of workers' remittances on equilibrium real exchange rates (ERER) in recipient economies. Using a small open economy model, it shows that standard "Dutch Disease" results of appreciation are substantially weakened or even overturned depending on: degree of openness; factor mobility between domestic sectors; counter cyclicality of remittances; the share of consumption in tradables; and the sensitivity of a country's risk premium to remittance flows. Panel cointegration techniques on a large set of countries provide support for these analytical results, and show that ERER appreciation in response to sustained remittance flows tends to be quantitatively small.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet